EFEKTIVITAS DAN EFISIENSI PENGELOLAAN TENAGA PENDIDIK DAN KEPENDIDIKAN MELALUI TEKNOLOGI INFORMASI DAN KEPEMIMPINAN - Yelvira, Yelvira; Sriwahyuni, Eci (UIN Imam Bonjol Padang, 2024)
Educators and educational staff are essential resources in supporting the success of the teaching and learning process in schools.Therefore, they must be managed effectively, and their management can not be separated from the role of a leader.This study is a literature review conducted using the Systematic Literature Review (SLR) method, consistingof six stages: planning, literature search, inclusion and exclusion criteria assessment, quality assessment, data collection, and data analysis.This study aims to identify supporting factors, the contribution of information technology to improving the effectiveness and efficiency of managing educators and educational staff, and the role of leadership in overcoming obstacles in managing these resources.The results of data analysis indicate that the effectiveness and efficiency of managing educators and educational staff are influenced by adequate infrastructure, competency of educators and educational staff, integrated information technology, effective leadership, clear task allocation, good communication,and performance monitoring and evaluation. Information technology supports more efficient management through administrative automation, rapid data access, and transparent financial management. Leadership plays a strategic role in providing direction, support, and innovation, thus overcoming administrative challenges, boosting motivation, and strengthening coordination among related parties.